Optimizing CNC Frame Machining for Low Voltage Motors: A Production Efficiency, Cost, and Capacity Analysis - Nyholm, Max (My University, 2026)
The global demand for high-efficiency low-voltage electric motors is continuously increasing and that put pressure on manufacturers to optimize their production capacity while managing oper ational costs, energy consumption, and equipment reliability. Despite wide literature on CNC machining optimization, no similar research exists specifically focusing on electric motor frame machining. This thesis addresses that gap through a quantitative case study done at a manufac turing company in Finland. The study investigates CNC machining efficiency at two vertical machining centres, one 1992 model (120-1) and one 2007 model (120-4). The author applies Overall Equipment Effectiveness (OEE), Total Cost of Ownership (TCO), and Lean manufacturing frameworks to analyse costs, process efficiency, downtime, and production capacity over 2024–2026. Data collection com bined internal database analysis, semi-structured interviews, process observation, and manual time studies. The researcher's three years of working experience at the case company as a maintenance mechanic, maintenance supervisor, and production development engineer pro vided essential knowledge for collecting data from systems and adapting theoretical frameworks to this specific manufacturing context. The analyzs examines the main cost drivers in CNC frame machining, including operator labour, maintenance, tool wear, cutting liquid, and energy consumption. The process efficiency analysis identifies the key sources of non-value-added time at both task level and the shift level, and compares theoretical versus actual production capacity for the CNC-machines. Maintenance performance is evaluated using key performance indicators including Mean Time to Failure, Mean Time to Repair, Mean Time Between Failures, and Mean Downtime. Based on the findings, a capacity forecasting model is developed for the case company, enabling estimation of future production volumes by adjusting parameters related to machine reliability, process times, and operational schedules. Practical recommendations are provided for improv ing maintenance strategy, optimising tool change, reducing non-value-adding process time, and supporting investment decision-making for future capacity expansion. Suggestions for future re search and the limitations of the study are also discussed.

Den globala efterfrågan på effektiva lågspänningselektromotorer ökar kontinuerligt, vilket sätter press på tillverkare att optimera deras produktionskapaciter samtidigt som de ska hantera driftskostnader, energiförbrukningar och utrustningens driftpålitlighet. Trots omfattande litteratur om optimering av CNC-bearbetning finns inte liknande forskningar som specifikt behandlar CNC-bearbetning av elmotorers ramar. Detta examensarbete fyller den luckan genom en kvantitativ studie genomförd vid ett produktions företag i Finland. Studien undersöker CNC-bearbetningseffektiviteten vid två vertikala bearbetningsmaskiner, en modell från 1992 (120-1) och en modell från 2007 (120-4). Författaren tillämpar ramverken Overall Equipment Effectiveness (OEE), Total Cost of Ownership (TCO) och Lean-tillverkning för att analysera kostnader, processeffektivitet, driftstopp och produktionskapacitet under åren 2024–2026. Datainsamlingen kombinerade analys av interna databaser, semistrukturerade intervjuer, processobservationer och manuella tidsstudier. Skribentens tre åriga arbetserfarenhet vid företaget som underhållsmekaniker, underhållschef och produktionsutvecklingsingenjör gav nödvändig kunskap för att samla in data från systemen och anpassa de teoretiska ramverken till detta specifika tillverkningssammanhang. Analysen granskar de viktigaste kostnadsdrivarna vid CNC-bearbetning av ramar, inklusive operatörslöner, underhåll, verktygsslitage, skärvätskor och energiförbrukning. Processeffektivitetsanalysen identifierar de viktigaste källorna till icke-värdeskapande tid på både uppgifts- och skiftnivå, samt jämför den teoretiska produktionskapaciteten med den faktiska för CNC-maskinerna. Underhållsprestandan utvärderas med hjälp av nyckelindikatorer, inklusive medelfel-till-fel-tid, medeltid för reparation, medeltid mellan fel och medel nedtid. Baserat på resultaten utvecklas en kapacitetsprognosmodell för fallföretaget, som möjliggör uppskattning av framtida produktionsvolymer genom justering av parametrar relaterade till maskiners tillförlitlighet, processtider och driftsscheman. Praktiska rekommendationer ges för att förbättra underhållsstrategin, optimera verktygsbyten, minska icke-värdeskapande processtid och stödja investeringsbeslut för framtida kapacitetsutbyggnad. Förslag till framtida forskning och studiens begränsningar diskuteras också.
Keywords: machine tools; efficiency (properties); production; costs; industry; machines; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management